Synthesis of cyclic alkenyl dimethylsiloxanes from alkynyl benzyldimethylsilanes and application in polyene synthesis - Gudmundsson, HG; Kuper, CJ; Cornut, D; Urbitsch, F; Elbert, BL; Anderson, EA (American Chemical Society, 2019)
Cyclic dimethylalkenylsiloxanes, useful motifs for (Z)-selective Hiyama cross-coupling, are accessed from alkynyl benzyldimethylsilanes featuring adjacent allylic or homoallylic oxygen substituents by semihydrogenation/debenzylation/cyclization. While formation of 5- and 6-membered rings can be achieved from the free alcohols using fluoride or silanolate, allylic acetate precursors to 5-membered rings display distinct modes of activation. The utility of these compounds is demonstrated through the preparation of a variety of (Z)-alkene-containing polyenes and application to a concise total synthesis of leukotriene B3.